Overcoming microbial hurdles: keeping the Olympics infection-free - Bishop, N. C. (Future Microbiology, 2012)
In the coming weeks, over 11,000 athletes are expected to arrive in the UK for the XXX Olympic Games and XV Paralympic Games, or as it is more commonly known, London 2012. The arrival of so many athletes, coaches and other support staff from over 200 nations, many of which will be living in close proximity in the Olympic Village, provides an ideal environment for the transmission of infectious diseases. Of course, this situation is not uncommon for any large gathering, but for the athletes arriving in London over the next few weeks, this is the culmination of years of hard work, dedication and sacrifice for the chance to perform (and hopefully win) on the Olympic stage. Contracting an infection at any time can lead to absence from training and impaired performance. Contracting an infection during the Games can be devastating.